Between habitus and dépaysement: a decolonial perspective on Rio de Janeiro Catacumba favela - ANDERSON DE SOUZA SANT’ANNA (Cadernos EBAPE.BR)
Abstract This article explores the application of Bourdieu’s concepts of habitus and dépaysement within the Catacumba favela in Rio de Janeiro, Brazil, drawing insights from Janice Perlman’s research. It examines the influence of various strategies - such as stereotyping, mythification, cooptation, uprooting, disenchantment, and coercion - on the traditional structures of housing, social aggregation, and socialization within the favela. Moreover, the study extends its focus to extract potential lessons and insights from these observed dynamics, particularly for marginalized populations living in the global periphery. Briefly, the study revisits Perlman’s seminal research on favelas through Bourdieu’s theoretical framework to uncover the historical roots of current social dynamics and their relevance for understanding decolonial practices in contemporary urban contexts. The findings offer valuable contributions to understanding the disruptive impacts of social structures and emphasize the importance of addressing these issues in both organizational strategies and public policies. By revisiting the Catacumba experience, the study also sheds light on the development of local leaders and the mobilization of distinctive forms of capital within these marginalized communities. Furthermore, it makes a significant contribution to decolonial studies by examining historical and contemporary colonization processes and forms of resistance within marginalized communities. By exposing and challenging the enduring colonial legacies that continue to shape the lives of marginalized populations, it offers insights into how these communities resist and navigate such legacies, contributing to the broader discourse on decolonization and the rejection of colonial structures.